Conceptual Foundations of Property Rights: Rethinking De Facto Rural Open Access to Common-Pool Resources in Ethiopia - Stebek, EN (Mizan law review, 2011)
This article, inter alia, attempts to highlight some major concepts and theories on property and the rationales and elements of property rights. It also briefly deals with the distinction between property rights on the stock of resources and its flows, and indicates the downsides of open access in the efficient utilization and sustainability of common-pool resources. Where de jure public property becomes de facto open access, certain common-pool resources in the rural areas of Ethiopia (such as forests) are exposed to encroachment, unlawful logging and overgrazing. The article attempts to show that it is usually impossible to effectively exclude persons from the use and overconsumption of commonpool resources in Ethiopia in the absence of well-defined and effectively implemented public property regime, or unless the property rights of indigenous communities and collectives such as peasant associations are duly recognized and clearly defined so that the right holders can have vested interest in the preservation, protection and development of these resources. Key words: Property rights, rural open-access, common property, public property, common-pool resources, Ethiopia.